2021
DOI: 10.3390/toxins13040267
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Multiple Mycotoxins in the Qatari Population and Their Relation to Markers of Oxidative Stress

Abstract: Mycotoxins are naturally occurring food toxins worldwide that can cause serious health effects. The measurement of mycotoxin biomarkers in biological fluids is needed to assess individual's’ exposure. The aim of this study was to investigate the incidence of mycotoxins in the Qatari population. Serum samples from 412 adults and urinary samples from 559 adults were analyzed for the presence of mycotoxin biomarkers. Multimycotoxin approaches have been applied, using liquid chromatography mass spectrometry method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Regarding AFs results, previous studies showed that despite being regulated, AFs are still found in human urine but with low incidence, as presented in this study in Table 6 (1–2%). Values are in accordance with a recent study by Al-Jaal et al [ 15 ] analyzing different biological samples of the Qatari population employing HPLC-MS/MS, being lower than 3% for AFB1, AFB2, and AFG2 with concentrations <LOQ for AFB1 and AFB2 and 0.19–0.34 ng/mL for AFG2, finding less mycotoxin incidence in urine than in plasma. In a study of 94 samples in Portugal, AFB1 had an incidence of 12%, followed by AFB2 (3%), AFG2 (3%), and AFG1 (2%) [ 50 ], and similar results were obtained by Foerster et al [ 51 ] who detected AFB1 in 8% of samples.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding AFs results, previous studies showed that despite being regulated, AFs are still found in human urine but with low incidence, as presented in this study in Table 6 (1–2%). Values are in accordance with a recent study by Al-Jaal et al [ 15 ] analyzing different biological samples of the Qatari population employing HPLC-MS/MS, being lower than 3% for AFB1, AFB2, and AFG2 with concentrations <LOQ for AFB1 and AFB2 and 0.19–0.34 ng/mL for AFG2, finding less mycotoxin incidence in urine than in plasma. In a study of 94 samples in Portugal, AFB1 had an incidence of 12%, followed by AFB2 (3%), AFG2 (3%), and AFG1 (2%) [ 50 ], and similar results were obtained by Foerster et al [ 51 ] who detected AFB1 in 8% of samples.…”
Section: Discussionsupporting
confidence: 92%
“…Human biomonitoring (HB) is a scientific technique recently applied in several recent multi-mycotoxin studies [ 15 , 16 , 17 , 18 , 19 ]. Analysis of mycotoxins in human urine is a suitable alternative to assess the exposure assessment to mycotoxins since most of them and their metabolites are efficiently excreted in this biological matrix [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxin toxicity has been linked to molecular mechanisms, including oxidative stress and free radical accumulation [35,36]. DNA, lipids, and proteins can be chemically impaired by free radicals and antioxidants during mycotoxin exposure [37][38][39]. Our study suggests that FXN may be a novel factor influencing hepatic tissues' pathological condition following ZEA exposure.…”
Section: Discussionmentioning
confidence: 74%
“…In humans, both α- and β-zearalenol can be detected, but β is the dominant. In pigs, cows and ducks, α-zearalenone is prevalent [ 14 , 15 , 16 ]. The conversion between ZEA and its metabolites mainly occur in the intestinal tract and bacteria of this system have a key role in this conversion; for this reason the toxin appears quickly in the feces [ 4 ].…”
Section: Occurrence Of Zearalenone In Food and Feedmentioning
confidence: 99%